2008
DOI: 10.1038/cmi.2008.44
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Suppresses Cytotoxicity and Proliferative Capacity of Murine Splenic NK1.1+ Cells

Abstract: In order to clarify the effects of 17β-estradiol (E2) on natural killer (NK) cells and the possibly regulatory mechanisms, we obtained highly purified and viable NK cells from C57BL/6J mouse spleen by a magnetic cell sorter (MACS). These cells were treated with E2 and then their cytotoxicity and proliferative capacity were examined. To further investigate the mechanisms on the effect of E2 on NK cells, expressions of activationassociated markers (CD69, CD122) and inhibitory receptors (CD94, Ly49), and intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…17b-estradiol can suppress the cytotoxicity and proliferative capacity of murine splenic NK1.1 in vitro. 32 The interaction between NKG2DL and NKG2D plays an important role in immune surveillance, and MICA/B are ligands for NKG2D.…”
Section: Discussionmentioning
confidence: 99%
“…17b-estradiol can suppress the cytotoxicity and proliferative capacity of murine splenic NK1.1 in vitro. 32 The interaction between NKG2DL and NKG2D plays an important role in immune surveillance, and MICA/B are ligands for NKG2D.…”
Section: Discussionmentioning
confidence: 99%
“…11 Some reports also indicated that P4 can suppress lytic activity of uNK cells and enhanced the expansion of the CD56 + population in endometrial leucocytes. 11 Some reports also indicated that P4 can suppress lytic activity of uNK cells and enhanced the expansion of the CD56 + population in endometrial leucocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that 17b-Estradiol (E2) could suppress cytotoxicity and proliferative capacity of murine splenic NK1.1 + cells. 11 Some reports also indicated that P4 can suppress lytic activity of uNK cells and enhanced the expansion of the CD56 + population in endometrial leucocytes. 12,13 Although peripheral blood NK cells express progesterone receptors (PR), 14 uNK cells do not express PR in both women and mice.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies imply that, on one hand, "low-dose" estrogen increases antibody production [41][42][43] and autoimmunity [44,45], while on the other hand, it decreases T-cell mediated delayed-type hypersensitivity (DTH) [41,[46][47][48], suppresses leukocyte production in the bone marrow and granulocyte-mediated inflammation [49] as well as natural killer (NK)-cell mediated cytotoxicity [43,50,51]. Mammalian cells express 2 receptor isoforms for estrogen receptor (ER), ERα and ERβ [52], although their relative contribution to estrogen-mediated changes in hematopoiesis is still under considerable debate [53].…”
Section: Gonadal Steroid Hormones Regulate Immune Responsesmentioning
confidence: 99%